Post‐vaccination healthcare attendance rate as a proxy measure for syndromic surveillance of adverse events following immunisation - Yonatan Moges Mesfin; Allen C. Cheng; Joanne Enticott; Jock Lawrie; Jim Buttery (Elsevier, 2021)
Abstract Objective: This study explored whether all‐cause healthcare attendance rate post‐vaccination could detect the two historical influenza safety episodes occurring in 2010 and 2015 using a large de‐identified general practitioner (GP) consultations dataset. Methods: A retrospective observational cohort study was conducted using GP consultation data routinely collected from 2008 to 2017 in Victoria, Australia. Post‐vaccination GP consultation rates were monitored, over a 22‐week surveillance period each year that aligned with each year's influenza vaccination season, using the Observed minus Expected (O‐E) and the Log‐Likelihood Ratio (LLR) CUSUM charts. Days 1-7 post‐vaccination were considered as the risk period. The LLR CUSUM was designed to detect both a 50% and two‐fold rise in the odds of the baseline post‐vaccination GP consultation rates. Results: Over the 10‐year study period, more than 1.5 million seasonal influenza vaccines doses were administered to 295,091 persons. Overall, 1.29% had a GP consultation within one week of vaccination, but 98.53% of the consultations occurred in days 1-3 post‐vaccination. The LLR CUSUM chart detected significant increases in the weekly rates of post‐vaccination GP consultation in 2010 in children aged under ten years and in 2015 in adults aged 19-64 years. These increases were aligned by week, but one week earlier and by age category, with the historical adverse events following immunisation (AEFI) signals occurring in 2010 and 2015. However, in the absence of historical AEFI signals, increased rates of post‐vaccination GP consultations were identified in three of the eight influenza vaccination years. Conclusion: The crude post‐vaccination healthcare attendance rate has the potential to offer a sensitive proxy to monitor vaccine safety signal. Implications for public health: Vaccine safety monitoring using syndromic indicator has the potential to augment the existing surveillance systems as part of an integrated vaccine safety monitoring approach.